The fertilizing role of African dust in the Amazon rainforest: A first multiyear assessment based on data from Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite Observations. Issue 6 (18th March 2015) - Yu, Hongbin; Chin, Mian; Yuan, Tianle; Bian, Huisheng; Remer, Lorraine A.; Prospero, Joseph M.; Omar, Ali; Winker, David; Yang, Yuekui; Zhang, Yan; Zhang, Zhibo; Zhao, Chun
Abstract The productivity of the Amazon rainforest is constrained by the availability of nutrients, in particular phosphorus (P). Deposition of long‐range transported African dust is recognized as a potentially important but poorly quantified source of phosphorus. This study provides a first multiyear satellite‐based estimate of dust deposition into the Amazon Basin using three‐dimensional (3‐D) aerosol measurements over 2007–2013 from the Cloud‐Aerosol Lidar with Orthogonal Polarization (CALIOP). The 7 year average of dust deposition into the Amazon Basin is estimated to be 28 (8–48) Tg a−1 or 29 (8–50) kg ha−1 a−1. The dust deposition shows significant interannual variation that is negatively correlated with the prior‐year rainfall in the Sahel. The CALIOP‐based multiyear mean estimate of dust deposition matches better with estimates from in situ measurements and model simulations than a previous satellite‐based estimate does. The closer agreement benefits from a more realistic geographic definition of the Amazon Basin and inclusion of meridional dust transport calculation in addition to the 3‐D nature of CALIOP aerosol measurements. The imported dust could provide about 0.022 (0.006–0.037) Tg P of phosphorus per year, equivalent to 23 (7–39) g P ha−1 a−1 to fertilize the Amazon rainforest. This out‐of‐basin phosphorus input is comparable to the hydrological loss of phosphorus from the basin, suggesting an important role of African dust in preventing phosphorus depletion on timescales of decades to centuries.